THE RELATIONSHIP BETWEEN HUSBAND SUPPORT AND MASS MEDIA ON THE USEGE OF CONTRACEPTIVE TOOLS IN LANGARA PUBLIC HEALTH CENTER, ISLAND KONAWE DISTRICT : USAGE OF CONTRACEPTIVE TOOLS - Irfan Chandra; Tasnim Tasnim; Fatmawaty Fatmawaty (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: Based on an initial survey  in Langara communities showed that from 15 communities in Langara Health Center, their husband gave  les support to use a contraceptive tool. Then the mothers said that because of the lack of support from their families with the reason that their husbands complained during sexual intercourse, the husbands were afraid of the side effects of contraception used by their wives. Some of the mothers said they had an unpleasant experience due to weight changes. In addition, the Langara community still lacks knowledge about contraceptives, health facilities are still far from residents' homes. The use of contraceptives plays an important role as the main decision maker regarding the choice of contraception.This study aims to analyse the relationship between husband support and mass media on the usage of contraceptive tools in Langara Public Health Centre in Island Konawe District. Methods: Type of quantitative research with cross sectional approach. The population in this study were all families who were in the working area of the Langara Health Center as many as 2,007 families. A sample of 331 people with sampling using the Lemeshow formula. Results: The results of the statistical test of the husband's support variable show the value of X2 count = 18.21 > X2 table = 3.841 and the value of Phi (Φ) = 0.354 and the mass media variable X2 count = 16,426 > X2 table = 3.841 and the value of Phi (Φ) = 0.522. Conclusion: There is a relationship between husband's support and mass media with the use of contraceptives in the work area of the Langara Health Center, Konawe Islands Regency.